2015
DOI: 10.1162/jocn_a_00818
|View full text |Cite
|
Sign up to set email alerts
|

The Past Tense Debate Revisited: Electrophysiological Evidence for Subregularities of Irregular Verb Inflection

Abstract: Neuropsychological research investigating mental grammar and lexicon has largely been based on the processing of regular and irregular inflection. Past tense inflection of regular verbs is assumed to be generated by a syntactic rule (e.g., show-ed), whereas irregular verbs consist of rather unsystematic alternations (e.g., caught) represented as lexical entries. Recent morphological accounts, however, hold that irregular inflection is not entirely rule-free but relies on morphological principles. These subregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…In contrast to Experiment 1, the results of Experiment 2, in which a syntactic judgement task was used that directly drew the participants' attention to the critical verbs and, thus, triggered the subjects to carry out a syntactic evaluation, revealed significant ERP results. While the effect we found in our study was a broadly distributed negativity similar to an N400, the ERP components observed in similar studies by Regel et al [12], [18] were a biphasic LAN-P600 pattern. The latter was clearly associated with syntactic processes; however, our results indicate a different neural processing.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In contrast to Experiment 1, the results of Experiment 2, in which a syntactic judgement task was used that directly drew the participants' attention to the critical verbs and, thus, triggered the subjects to carry out a syntactic evaluation, revealed significant ERP results. While the effect we found in our study was a broadly distributed negativity similar to an N400, the ERP components observed in similar studies by Regel et al [12], [18] were a biphasic LAN-P600 pattern. The latter was clearly associated with syntactic processes; however, our results indicate a different neural processing.…”
Section: Discussionsupporting
confidence: 75%
“…Regel, Opitz, Müller and Friederici [12] manipulated German irregular verbs embedded in minimal syntactic contexts (i.e. phrases).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gries seems to uphold the idea that whole-unit frequency effects -if real, though not in the present case -automatically counts against compositionality. This is a dogma from the past tense debate as pointed out in the target article; see Yang (2002), Taft (2004), Fruchter and Marantz (2015), Regel et al (2015) for acquisition, processing, and neurological evidence for compositional approaches to whole-unit frequency effects.…”
Section: Clarifications and Correctionsmentioning
confidence: 99%